John Donne's metaphors of self and empire: a cognitive analysis - Sohrabi, Zohreh; Pirnajmuddin, Hossein (Penerbit Universiti Kebangsaan Malaysia, 2017)
Donne's strategies to win the authority of the 'domain' of love in his poetry are attempts to claim a personal domain for himself. This essay focuses on this personal domain in order to analyse the concept of self in Donne's poetry. Lakoff and Johnson's discussion about the basic metaphors embedded in our childhood by which we conceptualise the notion of self presents the cognitive bases of Donne's different metaphors of self. Significantly, as a poet of late Renaissance, Donne's metaphors have close association with imperial and colonial patterns. Combining insights from cognitive poetics and Edward Said's views about culture and imperialism, the writers try to look into the way the poet uses these metaphors to fashion a sense of communal/national identity. The essay will further focus on the multiple representations of self in Donne's poetry and the paradoxical signification of his identity.